A low‐frequency near‐field interferometric‐TOA 3‐D Lightning Mapping Array. Issue 22 (22nd November 2014) - Lyu, Fanchao; Cummer, Steven A.; Solanki, Rahulkumar; Weinert, Joel; McTague, Lindsay; Katko, Alex; Barrett, John; Zigoneanu, Lucian; Xie, Yangbo; Wang, Wenqi
Abstract We report on the development of an easily deployable LF near‐field interferometric‐time of arrival (TOA) 3‐D Lightning Mapping Array applied to imaging of entire lightning flashes. An interferometric cross‐correlation technique is applied in our system to compute windowed two‐sensor time differences with submicrosecond time resolution before TOA is used for source location. Compared to previously reported LF lightning location systems, our system captures many more LF sources. This is due mainly to the improved mapping of continuous lightning processes by using this type of hybrid interferometry/TOA processing method. We show with five station measurements that the array detects and maps different lightning processes, such as stepped and dart leaders, during both in‐cloud and cloud‐to‐ground flashes. Lightning images mapped by our LF system are remarkably similar to those created by VHF mapping systems, which may suggest some special links between LF and VHF emission during lightning processes.